2020
DOI: 10.2196/14865
|View full text |Cite
|
Sign up to set email alerts
|

Habits and Attitudes of Video Gaming and Information Technology Use in People with Schizophrenia: Cross-Sectional Survey

Abstract: Background Information technology and video gaming have potential advantages in the treatment of schizophrenia. However, information regarding the habits and attitudes related to internet use and video gaming in people with schizophrenia is limited. Objective The aim of this study was to explore the habits and attitudes regarding video gaming and information technology usage and their associated factors in people with schizophrenia in Hong Kong. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 79 publications
1
8
0
Order By: Relevance
“…The association of positive schizotypal traits with Puzzle type games is consistent with previous findings that patients with schizophrenia rated puzzle-type games as one of their top three preferred game genres (i.e., board/card games) ( Choi et al, 2020 ). Surprisingly, contrary to the predictions made here, positive schizotypal traits were not related to more socially oriented or fantasy-based genres such as RPG or Social Simulation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The association of positive schizotypal traits with Puzzle type games is consistent with previous findings that patients with schizophrenia rated puzzle-type games as one of their top three preferred game genres (i.e., board/card games) ( Choi et al, 2020 ). Surprisingly, contrary to the predictions made here, positive schizotypal traits were not related to more socially oriented or fantasy-based genres such as RPG or Social Simulation.…”
Section: Discussionsupporting
confidence: 90%
“…However, most studies have focused on action games, and no previous work has analyzed subclinical autistic and schizotypal traits (i.e., traits related to social cognition, neurodevelopment, and other phenotypes) together in relation to video game usage and preferences and their neurophysiological correlates. Such studies are important given the important roles of video games of diverse genres in human imaginative culture, and given that individuals with autism or schizotypy show some evidence of high rates of video game usage ( Mazurek and Engelhardt, 2013a , b ; Schimmenti et al, 2017 ; Choi et al, 2020 ; Menear and Ernest, 2020 ; Coutelle et al, 2021 ). This study thus analyzes how video game usage patterns, genre preferences, motivations, and reaction times are associated with measures of non-clinical autism and schizotypy.…”
Section: Introductionmentioning
confidence: 99%
“… Prikken et al (2019) identified the incorporation of interactive gaming features through a computer-based training program could help overcome amotivation among SZ as these elements were motivating and meaningful. Authors suggested that iVR and web-based gaming motivational features of being present in the simulated VE or gaming software could elicit emotional and motivational stimuli and foster the development of interpersonal skills in real-world situations ( Choi et al, 2020 ; Ku et al, 2007 ). Participants engaged more in the SST-VR group than the SST traditional role-play (SST-TR) group, which suggested that VR role-plays could increase motivation in SST ( Bisso et al, 2020 ; Park et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, web-based games involve playing online games that use principles of errorless learning, positive reinforcement, and self-instruction. The games were designed to address SZ social cognitive challenges (Choi et al, 2020; Gülkesen et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Rather than a reflection of technology causing or exacerbating psychosis expression, the explanation may lie in technological preference among individuals with psychotic experiences. This multifactorial preference could be motivated for example by the fulfillment of psychological needs, such as leisure, social connections or self-efficacy, or by the avoidance of in-person social interactions [54][55][56].…”
Section: Discussionmentioning
confidence: 99%